2020
DOI: 10.1007/s13595-020-00951-3
|View full text |Cite
|
Sign up to set email alerts
|

Performances of different methods of estimating the diameter distribution based on simple stand structure variables in monospecific regular temperate European forests

Abstract: & Key message Using the three characteristic points of a forest stand, dg (mean quadratic diameter), d min (diameter of the smallest tree) and d max (diameter of the largest tree), appears informative enough to determine the parameters of the whole diameter distribution and, hence, the standing volume, with an accuracy of 2-3%. This is related principally with a particular feature of the Weibull distribution function, and the empirical dependency of the main scale parameter α + β from the mean quadratic diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Thereby, the stand attributes are usually calculated based on entirely measured stands. However, Schütz and Rosset (2020) recently showed that a few simple stand attributes are informative enough to accurately determine the parameters of the diameter distribution at the stand scale using a PPM approach. By forming one single log‐likelihood function over the characteristics of different stands, Cao (2004) developed a method (equation 13 in his paper) to generalise the parameter estimation in one likelihood function that enables proper estimation of uncertainty associated with the regression parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the stand attributes are usually calculated based on entirely measured stands. However, Schütz and Rosset (2020) recently showed that a few simple stand attributes are informative enough to accurately determine the parameters of the diameter distribution at the stand scale using a PPM approach. By forming one single log‐likelihood function over the characteristics of different stands, Cao (2004) developed a method (equation 13 in his paper) to generalise the parameter estimation in one likelihood function that enables proper estimation of uncertainty associated with the regression parameters.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing need for detailed forest attributes (e.g., tree lists) to answer regional questions, including understanding the current structure and succession status of a forest, formulating targeted forest management strategies for different forest regions, or predicting tree species distribution shifts under climate change (Ferraz et al 2020;Wang et al 2019), the development of efficient and accurate methods to obtain such regional tree list information has attracted significant research interest. Although previous studies have applied both parametric diameter distribution modeling (e.g., Weibull function) and nonparametric imputation (e.g., kNN model) to predict tree lists (Packalén and Maltamo 2008;Schütz and Rosset 2020;Shang et al 2017), the integration of these two methods proposed in our study is novel for generating wall-to-wall tree lists over large areas with limited forest inventory data. The Weibull function, especially the two-parameter Weibull function, is extensively used to describe the diameter distributions of single-and mixed-species stands (Hao et al 2022;Liu et al 2014;Schmidt et al 2020;Zhang et al 2018b).…”
Section: Selection Of the Coupled Framework For Predicting Wall-to-wa...mentioning
confidence: 99%
“…This approach usually uses a probability density function (PDF) (e.g., gamma, beta, exponential, log-normal, Johnson's SB, Weibull) to fit the diameter distribution for each stand and then predicts the PDF parameters using stand attributes (Liu et al 2009;Temesgen et al 2003). The two-parameter Weibull function has been reported to be the simplest and most accurate PDF for diameter distribution modeling for tree species worldwide, owing to its flexibility in describing different shapes of diameter distributions and fewer parameters (Diamantopoulou et al 2015;Schmidt et al 2020;Schütz and Rosset 2020). Schmidt et al (2020) modeled the diameter distributions of clonal eucalyptus stands in Brazil using a Weibull function and re-measured information from 56 permanent sample plots as predictor variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has proven to be a valuable replacement for the Spiegel Relaskop in rapid stand parameter estimations, with excellent accuracy in stands similar to ours (e.g., [17,18]). MOTI has been considered as a standard private forest stand inventory tool by several private forest enterprises in Switzerland [19], providing inexpensive stand parameter estimates needed for further simulations [20].…”
Section: Introductionmentioning
confidence: 99%